Local Stability and Structure of a Differentially Rotating Star of Non- Uniform Density - Singh, Kamal Krishan; Saini, Seema; Kumar, Sunil (Journal of Graphic Era University, 2023)
A <span dir="ltr" style="left: calc(var(–scale-factor)*82.46px); top: calc(var(–scale-factor)*307.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917815);" role="presentation">method is proposed to compute the <span dir="ltr" style="left: calc(var(–scale-factor)*229.25px); top: calc(var(–scale-factor)*307.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936265);" role="presentation">theoretical estimation of <span dir="ltr" style="left: calc(var(–scale-factor)*331.03px); top: calc(var(–scale-factor)*307.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899015);" role="presentation">physical parameters <span dir="ltr" style="left: calc(var(–scale-factor)*414.43px); top: calc(var(–scale-factor)*307.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968755);" role="presentation">and stability of differential <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*318.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942886);" role="presentation">rotation for <span dir="ltr" style="left: calc(var(–scale-factor)*119.30px); top: calc(var(–scale-factor)*318.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921958);" role="presentation">polytropic stars <span dir="ltr" style="left: calc(var(–scale-factor)*183.38px); top: calc(var(–scale-factor)*318.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921136);" role="presentation">including mass variation. <span dir="ltr" style="left: calc(var(–scale-factor)*286.25px); top: calc(var(–scale-factor)*318.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943033);" role="presentation">The law of differential rotation <span dir="ltr" style="left: calc(var(–scale-factor)*411.67px); top: calc(var(–scale-factor)*318.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893416);" role="presentation">is assumed to be in the form<span dir="ltr" style="left: calc(var(–scale-factor)*183.85px); top: calc(var(–scale-factor)*331.12px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">4 <span dir="ltr" style="left: calc(var(–scale-factor)*173.51px); top: calc(var(–scale-factor)*339.32px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">3 <span dir="ltr" style="left: calc(var(–scale-factor)*151.55px); top: calc(var(–scale-factor)*331.12px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">2 <span dir="ltr" style="left: calc(var(–scale-factor)*141.02px); top: calc(var(–scale-factor)*339.32px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">2<span dir="ltr" style="left: calc(var(–scale-factor)*119.36px); top: calc(var(–scale-factor)*339.32px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">1 <span dir="ltr" style="left: calc(var(–scale-factor)*82.95px); top: calc(var(–scale-factor)*331.12px); font-size: calc(var(–scale-factor)*6.87px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">2 <span dir="ltr" style="left: calc(var(–scale-factor)*97.70px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">)<span dir="ltr" style="left: calc(var(–scale-factor)*88.15px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">( <span dir="ltr" style="left: calc(var(–scale-factor)*177.95px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">s<span dir="ltr" style="left: calc(var(–scale-factor)*167.78px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">b<span dir="ltr" style="left: calc(var(–scale-factor)*145.65px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">s<span dir="ltr" style="left: calc(var(–scale-factor)*135.05px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">b<span dir="ltr" style="left: calc(var(–scale-factor)*114.18px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">b<span dir="ltr" style="left: calc(var(–scale-factor)*92.64px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation">s <span dir="ltr" style="left: calc(var(–scale-factor)*159.02px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation"><span dir="ltr" style="left: calc(var(–scale-factor)*126.28px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation"><span dir="ltr" style="left: calc(var(–scale-factor)*104.82px); top: calc(var(–scale-factor)*332.66px); font-size: calc(var(–scale-factor)*11.77px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation"> <span dir="ltr" style="left: calc(var(–scale-factor)*73.11px); top: calc(var(–scale-factor)*332.12px); font-size: calc(var(–scale-factor)*12.47px); font-family: sans-serif; transform: rotate(0.000026371deg);" role="presentation"> , t<span dir="ltr" style="left: calc(var(–scale-factor)*197.57px); top: calc(var(–scale-factor)*333.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920875);" role="presentation">he angular velocity of r<span dir="ltr" style="left: calc(var(–scale-factor)*289.97px); top: calc(var(–scale-factor)*333.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92111);" role="presentation">otation (ω) is a function of <span dir="ltr" style="left: calc(var(–scale-factor)*397.39px); top: calc(var(–scale-factor)*333.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908659);" role="presentation">distance (s) of the fluid element <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933911);" role="presentation">from the axis of rotation. <span dir="ltr" style="left: calc(var(–scale-factor)*174.38px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02);" role="presentation">Utilizing t<span dir="ltr" style="left: calc(var(–scale-factor)*215.45px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.843162);" role="presentation">he <span dir="ltr" style="left: calc(var(–scale-factor)*227.33px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89605);" role="presentation">concepts of Roche- <span dir="ltr" style="left: calc(var(–scale-factor)*307.25px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911075);" role="presentation">equipotential and <span dir="ltr" style="left: calc(var(–scale-factor)*379.03px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902888);" role="presentation">averaging <span dir="ltr" style="left: calc(var(–scale-factor)*421.03px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887145);" role="presentation">approach <span dir="ltr" style="left: calc(var(–scale-factor)*460.42px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of (<span dir="ltr" style="left: calc(var(–scale-factor)*474.58px); top: calc(var(–scale-factor)*348.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91901);" role="presentation">Kippenhahn <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923597);" role="presentation">and Thomas, 1970) <span dir="ltr" style="left: calc(var(–scale-factor)*155.66px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949902);" role="presentation">in a manner, earlier used by (S<span dir="ltr" style="left: calc(var(–scale-factor)*285.05px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957294);" role="presentation">aini, <span dir="ltr" style="left: calc(var(–scale-factor)*306.29px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.953117);" role="presentation">et al.<span dir="ltr" style="left: calc(var(–scale-factor)*326.95px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952333);" role="presentation">, 2012) <span dir="ltr" style="left: calc(var(–scale-factor)*360.19px); top: calc(var(–scale-factor)*360.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963901);" role="presentation">to incorporate the effects of differential <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*371.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956464);" role="presentation">rotation on the equilibrium structure of polytropic stellar models. <span dir="ltr" style="left: calc(var(–scale-factor)*343.39px); top: calc(var(–scale-factor)*371.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964295);" role="presentation">The inner structure of differentially <span dir="ltr" style="left: calc(var(–scale-factor)*492.22px); top: calc(var(–scale-factor)*371.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939351);" role="presentation">rotating <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941023);" role="presentation">polytropic models of a <span dir="ltr" style="left: calc(var(–scale-factor)*165.14px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909069);" role="presentation">star is demonstrated by calculating various physical parameters for <span dir="ltr" style="left: calc(var(–scale-factor)*435.91px); top: calc(var(–scale-factor)*383.33px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919773);" role="presentation">suitable combinations <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*394.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887764);" role="presentation">of parameters